Diels-Alder cycloaddition of oxidized furans and ethylene over supported heteropolyacid catalysts for renewable terephthalic acid - Fikri, Zuhroni Ali; Ha, Jeong-Myeong; Park, Young-Kwon; Lee, Hyunjoo; Suh, Dong Jin; Jae, Jungho (ELSEVIER, 2020)
The Diels-Alder reaction of biomass-derived dimethyl 2,5-furandicarboxylate (DMFDC) with ethylene followed by dehydrative aromatization is a sustainable route for the production of terephthalic acid, a monomer used for the synthesis of polyethylene terephthalate (PET). In this work, a series of heteropolyacid (HPA) catalysts with different supports, in this case SiO2, TiO2 and ZrO2, and hetero-addenda atoms, here phosphotungstic acid (HPW), silicotungstic acid (HSiW) and phosphomolybdic acid (HPMo), were used as catalysts, and their structure-activity correlation in the conversion of DMFDC to terephthalate was examined based on the density and strength of the acid sites. Characterization by XRD and Raman indicated that the Keggin structures of HPAs were well preserved on the SiO2 support compared to other supports, resulting in strong Bronsted acidity. The silica-supported HPW and HSiW catalysts exhibited significantly higher activity for terephthalate production than other supports and HPMo catalysts, but their activity were not correlated with the total acidity as measured by NH3-TPD. In contrast, the catalyst acid strength, as determined by the NH3 desorption temperature, decreased in the order HPW/SiO2 > HSiW/SiO2 > > HPW/ZrO2 > HPW/TiO2 > HPMo/SiO2 and was well correlated with the turnover rate for terephthalate production, suggesting that the higher activity of HPW/SiO2 is at least partly due to its stronger Bronsted acidity and that promoting the dehydration step of this reaction is a key to improving the selectivity to terephthalate. The effects of reaction conditions, in this case the acid loading amount, solvent used, temperature, and time, were also investigated with the most active silica-supported HPW catalysts to optimize the terephthalate yield. The 25%-HPW/SiO2 catalyst demonstrated a remarkable terephthalate yield of similar to 60% with almost complete conversion under the optimum condition.